Evaluación técnica del programa de recuperación de áreas degradadas en el corredor biológico paso de las lapas, Pacífico Central De Costa Rica. - Godínez-Serracín, Óscar (Instituto Tecnológico de Costa Rica, 2014)
Four reforestation projects for restoration of degraded lands in the Biological Corridor Paso de las Lapas, made by Fundación Árboles Mágicos were evaluated. Besides, was made the location by geographic coordinates of the projects and a proposal for potential reforestation areas in the biological corridor with native species. For silvicultural evaluation of reforestation projects, was used the methodology of Murillo, Badilla and Gallegos (2003), whereas for the proposal of new areas of reforestation were designed location maps, using the software ArcGis 10.1 y QGis 2.4.; is proposed that each selected potential area will serve as connection between forests. High mortality was determined in the four projects evaluated, presumably due to improper maintenance. All projects had few differences with the other variables evaluated. Concerning the proposal of new reforestation areas, were selected a total of 24 areas and for each one were recommended tree species according to climatic variables and altitude. In 7 of these areas is emphasized on species with importance as a food source and nesting site for the scarlet macaw (Ara macao).
Proyecto de Graduación (Licenciatura en Ingeniería Forestal). Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2014.
Keywords: Conectividad; Fragmentación; Plantaciones forestales; Manejo de cuencas; Evaluación de proyectos